2009
DOI: 10.1021/bi9007947
|View full text |Cite
|
Sign up to set email alerts
|

Base Pairing Configuration and Stability of an Oligonucleotide Duplex Containing a 5-Chlorouracil-Adenine Base Pair

Abstract: Inflammation-mediated reactive molecules can damage DNA by oxidation and chlorination. The biological consequences of this damage are as yet incompletely understood. In this paper, we have constructed oligonucleotides containing 5-chlorouracil (ClU), one of the known inflammation damage products. The thermodynamic stability, base pairing configuration and duplex conformation of oligonucleotides containing ClU paired opposite adenine have been examined. NMR spectra reveal that the ClU-A base pair adopts a geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 61 publications
4
39
0
Order By: Relevance
“…Analogous to m C, 5-bromocytosine ( Br C) stabilizes duplex formation when Br C-modified oligonucleotides are used. 5,8) Introduction of substituents at the C-5 position of uracil, such as a methyl group or halogen atoms, increases the stability of triplexes and duplexes formed 5,[9][10][11] (Fig. 1).…”
mentioning
confidence: 99%
“…Analogous to m C, 5-bromocytosine ( Br C) stabilizes duplex formation when Br C-modified oligonucleotides are used. 5,8) Introduction of substituents at the C-5 position of uracil, such as a methyl group or halogen atoms, increases the stability of triplexes and duplexes formed 5,[9][10][11] (Fig. 1).…”
mentioning
confidence: 99%
“…[14] We chose chlorouracil (c) as the most promising candidate for DNAbase transliteration (see Figure S1b) because: 1) it closely resembles thymine in structural studies of synthetic DNA duplexes, which suggests that the stability of the A:c pair is close to that of A:T; [15] 2) it is readily converted into the chlorodeoxyuridine nucleoside and the dcMP, dcDP, and dcTP nucleotides by nucleoside phosphorylases, thymidine kinase, thymidylate kinase, and nucleoside diphosphate kinase, respectively; [2] 3) unlike fluorouracil, it is less liable to elevated tautomerism, which causes ambiguous pairing with guanine as well as adenine; [15] 4) unlike the bromo and iodo analogues, it is not reduced to uracil at the redox potential of the cytoplasm. [16] Chlorine is present in numerous natural compounds, especially secondary metabolites of marine organisms, and a number of enzymatic mechanisms that enable the formation of C À Cl bonds have been elucidated.…”
mentioning
confidence: 99%
“…[30] Of these possibilities, formation of the anionic enol tautomer can be considered as a major factor that influences mispairing. The imino proton in chlorouracil (pK a = 7.9) is known to be more acidic than that in thymine (pK a = 9.7) but less acidic than in fluorouracil (pK a = 7.7), [15] which suggests that tautomerism Figure 3. Evolutionary kinetics of thymine replacement with chlorouracil in E. coli.…”
mentioning
confidence: 99%
“…Thermodynamic parameters were obtained by fitting the experimental melting curves or from a plot of 1/ T m versus lnCt obtained at different oligonucleotide concentrations (Ct) as described previously (32, 33; Supporting Information Figure S2). The experimental values obtained in this study for the oligonucleotides shown in Figure 1 are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%